KETERAWETAN 41 JENIS KAYU TERHADAP BAHAN PENGAWET CCB - Sasa Abdurrohim; Didik Achmad Sudika (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Most of the Indonesian wood species exhibit a wide differences in treatability. This may reduce effectiveness in loading several wood species simultaneously. This study investigated treatability of 41 wood species through full-cell process using CCB (copper-chrome-boron) preservatives.Representative wood samples, measuring 5 cm wide, 5 cm thick and I 00 cm long were preparedfrom each species and then remain to reach the air-dry condition. Pressures imposed during the process were consisted of initial and final vacuum al 500 mm Hg for 15 minutes, and a hydraulicpressure of 10 atmospheresfor 60 minutes.The results revealed that 20 of the study species were classified easy, I 2 species were moderate, 5 species were difficult, and the remaining 4 species were very difficult. Wood species within the class could be treated simultaneously. Results also indicated that there were great variations of chemical retention within the same class of penetration.